Annexe I : Sigles (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Annexe II : Bibliographie (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Chronologie de la Législation Québécoise en matière de relations de travail (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Divers (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Implantation manufacturière dans la région de Montréal (Relations industrielles / Industrial Relations, 1972)
This article reviews "Implantation manufacturière dans la région de Montréal" by Jean Claude Thibaudeau with the collaboration of Yvon Martineau.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Index — volume 27 — 1972 (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Introduction (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Notes explicatives (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Organisations gouvernementales (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Organisations gouvernementales (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Organisations professionnelles (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Organisations professionnelles (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Principaux collaborateurs (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Vocabulaire français-anglais des relations professionnelles (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Sam Gompers and the Expansion of the A.F. of L. into Canada, 1882-1898 - Babcock, Robert (Relations industrielles / Industrial Relations, 1972)
In the 1890's Gompers began dreaming of an international federation of labor, and became increasingly anxious to assert hegemony over organized labor in Canada. At the same time, some Canadians hoped to transform the Trades Congress into a Canadian federation of labor which would doubtless absorb, in time, the international union locals in Canada. Largely because Trades Congress leaders felt compelled to rely upon the Federation for funds and organizers, aC. F. of L. never came to pass, and Gompers was free to pursue his continentalist designs. The famous Berlin decisions of 1902 were rather clearly foreshadowed by the end of 1898.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Organizational Psychology, a Book of Readings - Beaulieu, Jean-Pierre (Relations industrielles / Industrial Relations, 1972)
This article reviews "Organizational Psychology, a Book of Readings" by David A. Kolb, Irwin M. Rubin and James M. McIntyre.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Organizational Psychology: An Experimental Approach - Beaulieu, Jean-Pierre (Relations industrielles / Industrial Relations, 1972)
This article reviews "Organizational Psychology: An Experimental Approach" by David A. Kobb, Irwin M. Rubin and James M. McIntyre.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Canadian Higher Education in the Seventies - Bélanger, Gérard (Relations industrielles / Industrial Relations, 1972)
This article reviews "Canadian Higher Education in the Seventies", a collection of abridged papers presented at a seminar sponsored by the Economic Council of Canada, the collection organized under the direction of Sylvia Ostry.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Labor Economics - Bélanger, Gérard (Relations industrielles / Industrial Relations, 1972)
This article reviews "Labor Economics" by R.B. Freeman.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Arbitration and Collective Bargaining : Conflict Resolution in Labor Arbitration - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1972)
This article reviews "Arbitration and Collective Bargaining : Conflict Resolution in Labor Arbitration" by Paul Prasow and Edward Peters.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les stratégies de développement organisationnel - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1972)
L'auteur tente de réaliser une mise en ordre des connaissances accumulées au cours de la dernière décennie dans le domaine du développement organisationnel. Après avoir établi une distinction entre approche globale et stratégies particulières, il procède à l'analyse de ces dernières pour en dégager la nature, les similitudes et les différences.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Organizations : Structure and Process - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1972)
This article reviews "Organizations : Structure and Process" by Richard H. Hall.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Questionnaire d’auto-évaluation du travail en équipe - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1972)
This article reviews "Questionnaire d’auto-évaluation du travail en équipe" by Solange Trudeau-Massé.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Canadian Labour Market, Readings in Manpower Economics - Belzile, Bertrand (Relations industrielles / Industrial Relations, 1972)
This article reviews "The Canadian Labour Market, Readings in Manpower Economics" by Arthur Kruger and Noah M. Meltz.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Collective Bargaining in Government (Readings and Cases) - Boivin, Jean (Relations industrielles / Industrial Relations, 1972)
This article reviews "Collective Bargaining in Government (Readings and Cases)" by J. Joseph Loewenberg and Michel H. Moskow.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Collective Bargaining in Public Employment and the Merit System - Boivin, Jean (Relations industrielles / Industrial Relations, 1972)
This article reviews "Collective Bargaining in Public Employment and the Merit System" from the U.S. Department of Labor.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La négociation collective dans le secteur public québécois : une évaluation des trois premières rondes (1964-1972) - Boivin, Jean (Relations industrielles / Industrial Relations, 1972)
Dans cette étude l'auteur décrit, analyse et critique les trois rondes de négociation que le Québec a connues dans le secteur public. Il en tire certaines conclusions générales.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Report of the Royal Commission on Labor Legislation in Newfoundland and Labrador - Boivin, Jean (Relations industrielles / Industrial Relations, 1972)
This article reviews "Report of the Royal Commission on Labor Legislation in Newfoundland and Labrador" by Maxwell Cohen and Joel Bell.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Broadcasting Labour Relations - Brody, Bernard (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Structures et pouvoirs de la Fédération des Travailleurs du Québec - Cardin, Jean-Réal (Relations industrielles / Industrial Relations, 1972)
This article reviews "Structures et pouvoirs de la Fédération des Travailleurs du Québec;" by Paul Bernard.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Some Attitudes Towards Retirement among Middle-Aged Employees - Crawford, Lawrence; Matlow, Jean (Relations industrielles / Industrial Relations, 1972)
The Ontario Longitudinal Study of Aging 1959-1978 interviewed 1,214 male employees at ages 48 and 54 on attitudes towards retirement, a suitable retirement age and views on not working. Replies at both ages are examined as well as some of the conditions which may have influenced attitudes towards retirement at age 54. Chi-square analysis indicated more employees were favourably disposed to retirement at age 54 than at the earlier age. Income level alone, of four factors studied, was positively related to attitudes towards retirement.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Taux de rentabilité attendu et la demande d’éducation - Crean, John F. (Relations industrielles / Industrial Relations, 1972)
L'abondante littérature sur la rentabilité des investissements privés en éducation, quoique très informative sur les effets économiques ultimes de ces investissements, nous renseigne très peu sur l'importance des aspects économiques de l'éducation dans les décisions privées des étudiants de s'instruire. Le but de la recherche décrite dans ce texte est de tracer les liens entre la demande privée pour l'éducation et les taux de rentabilité attendus par les étudiants d'école secondaire au Canada au début des années 1960.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La négociation collective en France - Dion, Gérard (Relations industrielles / Industrial Relations, 1972)
This article reviews "La négociation collective en France" by Gérard Adam, Jean-Daniel Reynaud and Jean-Maurice Verdier.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Imperfect Union - Dion, Gérard (Relations industrielles / Industrial Relations, 1972)
This article reviews "The Imperfect Union, A History of Corruption in American Trade Unions" by John Hutchinson
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’enquête par questionnaire : manuel à l’usage du praticien - Dionne, Pierre (Relations industrielles / Industrial Relations, 1972)
This article reviews "L’enquête par questionnaire : manuel à l’usage du praticien" by Claude Javeau.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Conciliation Procedures in Alberta - Dufty, Norman F. (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Growth of the Non-Institutional Response in the Canadian Industrial Sector - Flood, Maxwell (Relations industrielles / Industrial Relations, 1972)
In this paper, the author focuses on analyzing and explaining the widespread emergence of « non-institutional response ».
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La dépréciation de l’argent – solutions en droit du travail canadien - Gagnon, Jean-Denis (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le droit disciplinaire de la fonction publique - Garant, Patrice (Relations industrielles / Industrial Relations, 1972)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Status and Job Satisfaction of Computer Operators - Gluck, Adrian; Evans, Martin G. (Relations industrielles / Industrial Relations, 1972)
The results of this exploratory study suggest that computer operators experience a high level of inconsistency in their occupational status. Such inconsistency produces a differential impact upon the satisfaction of computer operators. When operators resolve the inconsistency by seeing their own status as low, they tend to be dissatisfied ; when they see their own status as high, they tend to be satisfied.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La rémunération objective des cadres et du personnel pour le Canada - Harker, H. John (Relations industrielles / Industrial Relations, 1972)
L'auteur attire l'attention sur certaines études en voie d'exécution, surtout en Grande-Bretagne, mais aussi en Amérique du Nord, laissant croire à l'existence d'une solution valable de rechange à la négociation collective en matière de relations du travail. Cette solution de rechange, la méthode dite de la période d'autonomie des initiatives pour mesurer les niveaux de travail et disposer les structures équitables de rémunération, fait l'objet d'un examen; ses inconvénients ainsi que ses répercussions pour le Canada sont mises en lumière.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Imaginer l’entreprise, nouvelles perspectives du management - Hubert, Gaétan (Relations industrielles / Industrial Relations, 1972)
This article reviews "Imaginer l’entreprise, nouvelles perspectives du management" by Michel Fustier.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les relations publiques, Pourquoi? Comment? - Hubert, Gaétan (Relations industrielles / Industrial Relations, 1972)
This article reviews "Les relations publiques, Pourquoi? Comment?" by Bernard Lecoq.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Individual or Collective Action? A Problem for Professional Engineers - Isbester, Fraser; Castle, Sandra (Relations industrielles / Industrial Relations, 1972)
In this article, the authors describe the different tendencies found in Ontario amoung Professional Engineers towards collective action. Should their negotiations with their employer s be based on law or only on voluntary recognition ?
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Race and Industrial Conflict - Laflamme, Gilles (Relations industrielles / Industrial Relations, 1972)
This article reviews "Race and Industrial Conflict" by Malcolm Rimmer.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Effective Management by Objectives - Langevin, Jean-Louis (Relations industrielles / Industrial Relations, 1972)
This article reviews "Effective Management by Objectives" by W.J. Reddin.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Satisfaction au travail : reformulation théorique - Larouche, Viateur; Delorme, François (Relations industrielles / Industrial Relations, 1972)
Dans cet article, les auteurs attribuent principalement la confusion qui gravite autour du thème de la satisfaction au travail à une carence manifeste au niveau du cadre conceptuel d'analyse. Ils proposent donc d'aborder la notion de satisfaction au travail par le biais d'une discussion approfondie de ses pôles principaux, c'est-à-dire les besoins humains et les incitations de l'emploi.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Communication et presse d’entreprise and Contribution à l’étude de la presse d’entreprise et essai de bibliographie - Lebel, Maurice (Relations industrielles / Industrial Relations, 1972)
This article reviews "Communication et presse d’entreprise" and "Contribution à l’étude de la presse d’entreprise et essai de bibliographie" both by Dimitri Weiss.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les relations du travail : employeurs, personnel, syndical, État - Lebel, Maurice (Relations industrielles / Industrial Relations, 1972)
This article reviews "Les relations du travail : employeurs, personnel, syndical, État" by Dimitri Weiss.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Economic Theory of Teams - Lemieux, Vincent (Relations industrielles / Industrial Relations, 1972)
This article reviews "Economic Theory of Teams" by Jacob Marschak and Roy Radner.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Industrial Democracy - McCaffrey, Gordon (Relations industrielles / Industrial Relations, 1972)
The purpose of this paper is to examine the concept of participation by workers in jobs and management and to come to some conclusions as to the role of industrial democracy, in Us various definitions, present and future, in Canadan Industrial Relations.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Technological Change and the CLC - McCaffrey, Gordon (Relations industrielles / Industrial Relations, 1972)
This paper presents a union position on Bill C-183 by looking at the pros and cons of this legislation and by examining what still needs to be done.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Unorganized Labour Versus Management: The Strike at the Chaudière Lumber Mills, 1891 - McKenna, Edward (Histoire sociale/Social History, 1972)
In the late summer of 1891, the Ottawa Valley timber traide was beset with labour problems. What had been an undercurrent of employee discontent quickly developed into a torrent of labour protest when twenty-four hundred men walked off their jobs in a dispute centered on the lumber mills of Hull and Ottawa at the region known as the Chaudiere. The action by these workers, who disrupted this important industry for almost five weeks, was probably the largest strike that had occurred in Canada up to that time. ...An analysis of the strike, however, exposes the attitudes of management, labour and community in such a confrontation, and provides valuable insights into the extent of labour activity in Canada in the last decades of the nineteenth century.

Union and Management Decision-Making in the Grievance Process - Peach, David A. (Relations industrielles / Industrial Relations, 1972)
Based on a study of five U.S. Steel Company, this paper explains union-management interactions in the grievance process.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le système des relations du travail chez les enseignants du secteur public québécois - Rainville, Jean-Marie (Relations industrielles / Industrial Relations, 1972)
Cette étude soutient l'idée qu'une organisation administrative ne peut s'étudier sans tenir compte de la relation existant entre elle et la société. À cet effet, l'utilisation non seulement de variables internes à l'organisation, mais aussi externes, sont nécessaires pour comprendre comment un groupe d'individus s'ajuste à l'organisation. L'auteur analyse ainsi le système des relations du travail dans une école régionale de la région métropolitaine de Montréal aux niveaux élémentaire et secondaire.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le prix de la santé - Rivard, Jean-Yves (Relations industrielles / Industrial Relations, 1972)
This article reviews "Le prix de la santé" by Jean-Luc Migué and Gérard Bélanger.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

A New View of Leisure - Ross, David P. (Relations industrielles / Industrial Relations, 1972)
The purpose of this paper is two-fold: first, an attempt is mode to define work and leisure in operational terms. Second, using the new definitions of work and leisure, several problems in economies are re-examined and an attempt is mode to illustrate how the new definition may give us new insights into old and current problems.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Training the Poor : A Benefit-Cost Analysis of Manpower Programmes in the U.S. Anti-Poverty Programme - Ross, David P. (Relations industrielles / Industrial Relations, 1972)
This article reviews "Training the Poor : A Benefit-Cost Analysis of Manpower Programmes in the U.S. Anti-Poverty Programme" by D.O. Sewell.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Droit du travail en vigueur au Québec - Roy, André (Relations industrielles / Industrial Relations, 1972)
This article reviews "Droit du travail en vigueur au Québec" by Robert Gagnon, Louis Lebel, and Pierre Verge.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les Mémoires d’Alfred Charpentier (Cinquante ans de vie ouvrière) - Roy, André (Relations industrielles / Industrial Relations, 1972)
This article reviews the autobiography "Les Mémoires d’Alfred Charpentier (Cinquante ans de vie ouvrière)".
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

White-Collar Workers - Roy, André (Relations industrielles / Industrial Relations, 1972)
This article reviews "White-Collar Workers" written in collaboration under the direction of Albert A. Blum.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les femmes dans la population active : 1970, faits et données - Sexton, Jean (Relations industrielles / Industrial Relations, 1972)
This article reviews "Les femmes dans la population active : 1970, faits et données" from the Bureau de la main-d’oeuvre féminine (Ottawa).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Manpower Planning and Programming - Sexton, Jean (Relations industrielles / Industrial Relations, 1972)
This article reviews "Manpower Planning and Programming" by Elmer H. Burack and James W. Walker.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Shutdown: The Impact of Plant Shutdown, Extensive Employment Terminations and Layoffs on the Workers and the Community - Sexton, Jean (Relations industrielles / Industrial Relations, 1972)
This article reviews "Shutdown: The Impact of Plant Shutdown, Extensive Employment Terminations and Layoffs on the Workers and the Community" by J.N. Eleen and A.G. Bernardine.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Determinants of Strike Activity in Canada - Smith, Douglas (Relations industrielles / Industrial Relations, 1972)
Strikes are an integral part of the collective bargaining process and as such must be understood in relation to their determinants in order to properly evaluate the performance of that process. In spite of the importance of such knowledge there has been surprisingly little effort devoted to estimating empirical relationships.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Corporate Team Training : A More Rational Organizational Development Method - Thrasher, Craig L. (Relations industrielles / Industrial Relations, 1972)
Problems of the increasing rates of failure of modem business organizations are examined, with particular emphasis given to firms in the «million dollar plus» category. On the hypothesis that this problem has evolved from an increasing inability of organizational members to make immediate and accurate decisions, various individual and organizational development methods are examined. A common failing of all of these methods is their inability to train individuals in team behavior— the essence of the business environment. A method of «Team Training» is described that should serve to close the gap between development of competent individuals and the growth of the responsive and successful business organization.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Technological Change and the Right to Strike - Woods, Harry Douglas (Relations industrielles / Industrial Relations, 1972)
A collective agreement covers only part of the relationship between the employees covered by the agreement and the employer. Some conflicts of interest not covered by the agreement may be resolved voluntarily by negotiation from time to time, but there remain conflicts of interest in which either no resolution can be worked out on one party, the employer, supported by the residual rights doctrine and the agreement, refuses to negotiate. The issue has become a matter of great public controversy in Canada in recent years and was highlighted by the technological change debate.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z